The South and The Grotesque: Flannery O’Connor’s ‘Twisted’ Characters - Tuğan, Abdullah Gökhan; Kocsoy, F. Gul (My University, 2020)
The objective of this article is to research the grotesque undertones of American South, investigatethe grotesque characters in Flannery O’Connor’s (1925-1964) short fiction based on WolfgangKayser’s (1906-1960) typology and accordingly reveal their affinities with the phenomenon ofviolence. The distinctive qualities of the South infuse all aspects of southern literature that is mostlynotable for its perennial emphasis upon the grotesque. As a significant southern writer, O’Connor alsoemploys grotesque characters in her fiction. O’Connor’s characters emanate grotesque singularities inthree different manners; corporeal malformation, intellectual incongruity and behaviouraldegeneration. These three motives for the grotesque are analyzed through three short stories in thisarticle: “Parker’s Back,” “The Comforts of Home” and “The Partridge Festival.”
Keywords: Edebi Teori ve Eleştiri